Scurvy: An elusive diagnosis - Michael Pope; Joshua Elder (Clinical Case Reports, 2023)
Key Clinical Message Scurvy is uncommon in the developed world, and clinical presentation may mimic other pathologic states. A thorough social and dietary history is essential to identifying patients at risk of vitamin C deficiency, which can then be easily treated. Abstract Scurvy is a disease of defective collagen synthesis that is characterized by easy bruising, gingival hemorrhages, poor wound healing, fatigue, and arthralgias. It is caused by dietary deficiency of vitamin C. This is the case of a patient with multiple risk factors for malnutrition who was diagnosed with scurvy.